The Little Red Sled - Hamilton, Tisha (New York : Scholastic, 2005)
Clifford loves his new sled. After the biggest snowfall of the year, he can't find it anywhere! Did Clifford lose the sled... or was it stolen?
Keywords: Female friendship -- Juvenile fiction; Trolls -- Juvenile fiction; Gems -- Juvenile fiction; Children's; Friendship -- Fiction; Trolls -- Fiction; Gems -- Fiction; Magic -- Fiction